Особенности образования древнеанглийских дифтонгов после инициальных палатальных согласных - Эабулене, Лайма (Kalbotyra, 1983)
The front consonants [j], g [ʒ́], [k’] and sc [sk’] caused diphthongization of the following front vowels \æ̌ ě\ to \ěa ı̌e\, respectively.In contradiction to the widely held opinion that the diphthongs [ı̌e] owe their origin to front mutation, we assume that their primary source was diphthongization after front consonants. It is also reasonable to assume that the initial stage of diphthongization might have touched all OE dialects. A similar allophonic development must not necessarily lead to the same phonological results.